Prevalence and Determinants of Wheezing and Bronchodilatation in Children With Cystic Fibrosis: A Retrospective Cohort Study - Galodé, Francois; Ladipo, O.; Andrieux, A.; Feghali, H.; Bui, S.; Fayon, Michael (Frontiers in Pediatrics, 2022)
BACKGROUND. Many patients with cystic fibrosis (CF) wheeze, and are dubbed as having CF-asthma. OBJECTIVE. Main: To evaluate the prevalence and characteristics of wheezing and a positive bronchodilatory response (BDR) in children with CF. Secondary: to identify the predictive markers of wheezing and BDR. METHODS. A retrospective single-center study in children with CF. We determined the characteristics of physician-reported wheeze in patients < 6 yrs, and BDR in patients aged 6 to 17 yrs. RESULTS. 125 preschool and 69 school-age children and adolescents with CF were included in the study. 71.2% of patients <6 yrs of age had had at least one episode of wheezing: 26.3% of patients were Transient Early Wheezers, 12.6% Late Onset Wheezers and 37.9% were Persistent Wheezers. The prevalence of a positive BDR was respectively 73.5%, 48.5% and 52.9% in the 6-8 yr, 10-12 yr and 15-17 yr age groups. In the 6-8 year old group, the sum of wheal diameters of allergic skin prick tests (SPT, to house dust mite, and cat or dog dander) was greater in those with BDR vs. no BDR (4 [2.0-8.8] vs. 1 [0-7.0] mm, p=0.01). The proportion of homozygous p.F508del patients was significantly lower in the group of patients who had wheezed by 6 years of age (60% vs 72.7%, p= 0.009), but conversely higher in the 6-8 yr old group with BDR vs. no BDR (64% vs 36%, p=0.04). Current wheezers at 6 yrs had a lower mean FEV1 of 91.5 + 4.4% vs. the non-current wheezers (100.9 + 2.4%; p=0.047). Similarly, FVC was significantly lower in the 6-8 yr old group with BDR vs. no BDR (85 ± 19 vs 101 ± 21%, p=0.015). CONCLUSION. Wheezing and BDR are very frequent findings in children with CF. Current wheeze at the age of 6 yrs was associated with worse lung function. Our findings suggest that a “CF-Asthma” denomination may be misleading in the majority of cases, and may lead to inappropriate treatment with inhaled steroids, in particular in preschool wheezers.